Saudi women's work challenges and barriers to career advancement. Issue 2 (8th May 2017) - Al-Asfour, Ahmed; Tlaiss, Hayfaa A.; Khan, Sami A.; Rajasekar, James
Abstract : Purpose: Few studies have explored the work challenges and career barriers faced by women in the Kingdom of Saudi Arabia (KSA). Drawing on Institutional Theory, the purpose of this paper is to explore the experiences of employed Saudi women through in-depth interviews. Design/methodology/approach: The paper employs a phenomenological qualitative approach drawing on 12 in-depth semi-structured interviews with Saudi women. Findings: The findings reveal a significant number of prominent societal and organizational structural and attitudinal barriers to the advancement of Saudi women in paid employment. Among others, these barriers include a lack of mobility; the salience of gender stereotypes; gender discrimination in the workplace; limited opportunities for growth, development, and career advancement; excessive workload caused by a lack of family-work balance; and gender-based challenges related to dealing with pregnancy. Research limitations/implications: Despite the contributions of this study, it also has limitations, particularly the convenience sampling approach and the focus on the KSA. The small sample size means that the findings cannot be generalized to all women employed in Saudi Arabia and should be generalized within Saudi Arabia and other Arab societies only with caution. Originality/value: The paper contributes to the understanding of work challenges and barriers of Saudi women in the workforce. It provides fresh insights to the issues surrounding women in Saudi Arabia and the need to address them in order to provide support for their career advancement.